Digitized card catalogs in Wrocław University Library - Wysokiński, Krzysztof (Biblioteka Uniwersytecka we Wrocławiu, 2015)
Digitized card catalogs in Wrocław University Library are developed alongside of the main source of the Library's resources, namely VIRTUA electronic catalog. The digitized card catalogs are tools informing about the collections which are still absent from the electronic catalog. Throughout 10 years of digitizing them the software employed to use them has been subject to many changes. To adjust to the increasing needs of the Library and user's requirements the software has been upgraded with additional storage modules to increase functionality of the whole system. The software is still being improved and enriched with new functions the aim of which is to enable users possibly the quickest access to the searched material out of the immense Library's stock. In the nearest future advantage is to be taken of text recognition technique in order to introduce more advanced searching methods (indexes, keywords). Attempts are also to be made to integrate digitized catalogs into other systems and services available in the Library.
Keywords: catalog cards; scanning; card catalogs; digitization; OCR